PEDIATRIC BRONCHIAL ASTHMA: MODERN TREATMENT ASPECTS - O.V. Zaitseva; О.А. Murtazaeva (Вопросы современной педиатрии)
Pediatric bronchial asthma is one of the most spread allergic diseases. There is a recent tendency of pediatric asthma morbidity increase, also among infants, as well as increase in its severity. That is why specialists all over the world are working upon new diagnostic methods and design of optimal therapeutic guidelines. This review contains main concepts of asthma treatment taking into account patient’s age and level of disease control. Optimal combinations of medications for basic treatment are also considered in this article as well as most promising asthma treating strategies.Key words: bronchial asthma, children, pharmaceutical treatment, inhaled glucocorticosteroids. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (6): 148–156)